Redwood Bend - Carr, Robyn (Don Mills, Ont. : MIRA Books, 2012)
Katie Malone and her twin boys' trip along the beautiful mountain roads to Virgin River is stopped short by a tire as flat as her failed romance. As she stands by the side of the road pondering her next move, Katie hears a distinct rumble. The sight of the sexy, leather-clad bikers who pull up beside her puts her imagination into overdrive.
Series volume number provided by cataloger.
Keywords: Man-woman relationships -- Fiction; Single parents -- Fiction; Motorcyclists -- Fiction; Virgin River (Imaginary place) -- Fiction; Love stories